2014
DOI: 10.1088/0965-0393/22/5/055019
|View full text |Cite
|
Sign up to set email alerts
|

On the accurate description of uranium metallic phases: a MEAM interatomic potential approach

Abstract: A new interatomic potential in the framework of the modified embedded atom method (MEAM) to model U metal is presented. The potential acceptably reproduces the lattice parameters and cohesive energy of the orthorhombic αU. The relative stability of the experimentally observed phase at low temperatures with respect to several other structures (bct, bcc, simple cubic, tetragonal β Np, fcc and hcp) is also taken into account. Intrinsic point defect properties compare reasonably well with data from the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…Recently, a Modified EAM (MEAM) potential [20] was published with the emphasis on defect migration energies. This potential predicted a new α↔γ transformation path and demonstrated that the diffusion mechanism in α-U is vacancy-controlled.…”
Section: Interatomic Potential For U With Improved Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a Modified EAM (MEAM) potential [20] was published with the emphasis on defect migration energies. This potential predicted a new α↔γ transformation path and demonstrated that the diffusion mechanism in α-U is vacancy-controlled.…”
Section: Interatomic Potential For U With Improved Performancementioning
confidence: 99%
“…Extrapolation of the elastic constants at room temperature to 0 K tends to increase [25,27], closing the gap between experiment and DFT calculations. Reference: a [20]; b [9]; c [17]; d [18]; e [25]; f [29]; g [30]; h [31]; i [32]; j [33]; k [26]; l [4]. increases in the whole temperature range while y decreases up to 700 K; at 800 K, the abrupt increase of y indicates the α  γ transformation is about to occur.…”
Section: Comparison Of the Comb And Eam Potentialmentioning
confidence: 99%
“…The pure Al interatomic potential fitted in this work adapts better to the context of the present study than previous others found in the literature [19][20][21]. This potential, together with a recently developed MEAM potential for pure U [22], are used to find an appropriate interaction for the Al-U alloy.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 73%
“…Calculated values of the expansion coefficients are a third to a half their corresponding experimentally observed values. It is worth to note that Al 4 U shows anomalous temperature behavior along the b lattice parameter as in the case of αU [22]. To the authors' knowledge, there is no experimental or theoretical evidence in the literature at this respect.…”
Section: Temperature Stability and Thermal Expansion Of The Al-u Intementioning
confidence: 88%
“…To this date both classical (CMD) [2,3,4,5] and quantum (QMD) [6,7] molecular dynamics have been used for investigation of uranium thermophysical properties. Although first-principles calculations give more accurate results, their immense computational cost makes the CMD approach more preferable for a study of phase diagrams of the actinides.…”
Section: Introductionmentioning
confidence: 99%